(untitled) (Academia Journal of Medicine, 2026)
Background Oral cancer is a major public health problem in India, with high morbidity and mortality largely due to late diagnosis. General dentists are often the first healthcare professionals to examine the oral cavity and thus play a critical role in early detection through routine oral cancer screening. Aim: To assess the knowledge, awareness, and clinical practices related to oral cancer screening among general dentists. Materials and Methods: A descriptive cross-sectional questionnaire-based study was conducted among 150 general dental practitioners. A validated, self-administered questionnaire comprising demographic details, knowledge, awareness, and practice-related questions was distributed. Data were analyzed using descriptive statistics and chi-square test to assess associations between variables. Results: Out of 150 participants, 62% demonstrated moderate knowledge, 24% had good knowledge, and 14% had poor knowledge regarding oral cancer screening. Although 78% were aware of oral cancer screening methods, only 46% reported performing routine oral mucosal examinations for all patients. Lack of training (48%) and time constraints (41%) were identified as major barriers. A statistically significant association was observed between years of clinical experience and knowledge scores (p < 0.05). Conclusion: While general dentists demonstrated fair awareness of oral cancer screening, gaps were observed in routine screening practices. Structured continuing dental education programs and hands-on training are recommended to enhance early detection and reduce oral cancer burden.